Effect of scan-path length on the scanning accuracy of completely dentate and partially edentulous maxillae - Waldecker, Moritz; Rues, Stefan; Behnisch, Rouven; Rammelsberg, Peter; Bömicke, Wolfgang (The journal of prosthetic dentistry, 2024)
Statement of problem - The accuracy of fit of fixed partial dentures is directly dependent on the accuracy of a digital scan. However, the influence of scan-path length on scanning accuracy is unclear. - Purpose - The purpose of this in vitro study was to evaluate how scan-path length influenced the scanning accuracy of a completely dentate or partially edentulous maxilla captured by 3 intraoral scanners: Omnicam AC (OC), TRIOS 4 (TR), and Primescan (PS). - Material and methods - Each intraoral scanner was used to make 30 scans each of the 2 clinical scenarios (completely dentate and partially edentulous) simulated with a reference model. The partially edentulous model simulated a maxilla with 6 prepared teeth to support a complete arch fixed partial denture. The missing teeth were then added to create a completely dentate model. The prepared teeth were later used to determine distance, angular, and tooth-axis deviations between the reference model (digitized with high precision before the tests) and the intraoral scans. Data were statistically analyzed by using a linear model or, if not applicable, a type II ANOVA (α=.05). - Results - Distance deviations increased linearly as the scan-path length increased. In contrast, angular and tooth-axis deviations did not increase linearly. All types of deviation differed depending on the scanning system used. Regarding the 90% quantile values, total distance deviations related to scan-path length amounted to 1.31 μm/mm (OC), 1.00 μm/mm (PS), and 1.45 μm/mm (TR) for the completely dentate maxilla and 1.10 μm/mm (OC), 1.46 μm/mm (PS), and 1.40 μm/mm (TR) for the partially edentulous maxilla. - Conclusions - Distance deviations became larger as the scan-path length increased.
Gesehen am 03.06.2024